Specifying the Domineering Role of Governance in the Long Term Environmental Excellence: A Case Study of Pakistan. (September 2022) - Arif, Muhammad; Chenghu, Zhang; Olah, Judit; Shehzad, Khurram; Ahmad, Mahmood
Pakistan is facing massive issues such as political instability, weak law enforcement, and corruption, leading to poor implementation of environmental policies. This research investigates the nexus among CO2 emissions, energy consumption, financial development, governance index, and economic growth under the framework of the Environmental Kuznets Curve (EKC) hypothesis. Moreover, the investigation also explores the impact of government effectiveness, voice and accountability, and regulatory quality from 1996Q4 to 2018Q4. The empirical statistics indicate that financial development and energy consumption incline environmental degradation, while the governance index negatively affects CO2 emission. The results validate the presence of the EKC hypothesis in Pakistan. Besides, political stability, control of corruption, and Government effectiveness assist in curbing environmental degradation. Our findings suggest that there is a need to strengthen the institutions, and the Government of Pakistan should control the corrupt practices related to environmental policy implementation and strictly monitor the Pakistan Environmental Protection Agency (PAK-EPA).